Exploring Vocational High School Students Speaking Anxiety: Causes and Proposed Strategies - Amanda Novi Wibisono; Zainul Aminin (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to provide an in-depth exploration of the causes of speaking anxiety and the strategies employed to overcome it among 11th grade students in a hospitality major. This research was conducted using qualitative design with 34 students from a vocational high school in Mojokerto as participants. The data were collected using open-ended questionnaires and semi-structured interviews to gather rich, detailed perspectives. The findings indicate that speaking anxiety is a multifactorial phenomenon. The primary causes identified include low English proficiency, lack of familiarity with tasks, lack of self-confidence, and fear of making mistakes. This study concludes that speaking is a complex challenge.